2009
DOI: 10.1007/s00420-009-0428-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of salivary cortisol as stress marker in ambulance service personnel: comparison between shifts working on mobile intensive care unit and patient transport ambulance

Abstract: Ambulance service personnel seem to be used to critical situations. There was few awareness of the "physiological" stress response indicating that stress is probably not perceived in work situations characterised by routines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
0
16
1
1
Order By: Relevance
“…All these constraints create physical, physiological and psychological demands before, during and after an emergency call-out. In accordance with Selye's theory,3 persistent exposure to stressors may progressively lead to overactivity of autonomic nervous system, resulting in various maladaptive outcomes, such as the development of mental health impairments, cardiovascular diseases (CVD), metabolic syndrome and obesity 4 5. Obesity may also be a risk factor for CVD in paramedics.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…All these constraints create physical, physiological and psychological demands before, during and after an emergency call-out. In accordance with Selye's theory,3 persistent exposure to stressors may progressively lead to overactivity of autonomic nervous system, resulting in various maladaptive outcomes, such as the development of mental health impairments, cardiovascular diseases (CVD), metabolic syndrome and obesity 4 5. Obesity may also be a risk factor for CVD in paramedics.…”
Section: Introductionmentioning
confidence: 82%
“…Also, higher secretion of cortisol in the morning was reported on days in emergency service than on days in patient transport, suggesting adjustment to forthcoming demanding tasks 4. It has been reported that paramedics who complained the most about pain and health problems had higher cortisol levels at work in the morning, than those with few complaints 6.…”
Section: Occupational Stress Indicatorsmentioning
confidence: 97%
“…We did not exclude non-menopausal women because basal cortisol levels do not differ during the menstrual cycle [31]. In addition, studies involving work stress and cortisol levels in acute care settings have mainly involved women [36,37,38,39]. …”
Section: Methodsmentioning
confidence: 99%
“…Wskazuje to na potrzebę dalszych analiz tego zagadnienia (25). Specyfika kierowania pojazdem uprzywilejowanym odbiega od zasad prowadzenia pojazdów prywatnych, a uczestnictwo w ruchu drogowym zespołów medycznych wiąże się z ogromnym ryzykiem i przeżywanym napięciem (26). Dotyczy to zarówno operatora pojazdu, jak i otoczenia, oraz obejmuje szereg konsekwencji prawnych, społecznych i zdrowotnych.…”
unclassified